Characterization and rheological properties of hybrid fillers filled high density polyethylene bio-composite / Noor Zuhaira Abd Aziz - Abd Aziz, Noor Zuhaira (Institute of Graduate Studies, 2017)
As the world tries to minimise possible harmful destruction of our environment and move towards GO GREEN Agenda, hybrid fillers have been widely used as alternative reinforcing filler for thermoplastic polymer composite. One of the most characteristic features of hybrid composite lies in its balanced performance of strength, as well as other properties, which include manufacturing cost. In this research, different fillers were used to obtain optimal hybrid composite composition from kenaf, rice husk (RH) and calcium carbonate (CaCO3). Different varying compositions up to 30 wt% of mixed kenaf and rice husk with CaCO3 were compounded with 40-70 wt% of high density polyethylene (HDPE) using twin screw extruded at 50rpm, to produce two different hybrid composites, HDPE/kenaf/CaCO3 and HDPE/rice husk/CaCO3. Properties of hybrid composites were compared between particulate CaCO3/kenaf fibrous form and CaCO3/rice husk particulate form. Hybrid composites were tested for physical, mechanical, thermal, burning rate and rheological behaviour. From test results, addition of filler had decreased melt flow index (MFI) up to 72% and increased density of hybrid composites up to 19%. In general, addition of both natural fibres, either kenaf or rice husk with CaCO3 decreased the tensile strength, elongation, and impact..